2012
DOI: 10.1016/j.anireprosci.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semen collection method (artificial vagina vs. electroejaculation), extender and centrifugation on post-thaw sperm quality of Blanca-Celtibérica buck ejaculates

Abstract: The aim of this study was to evaluate the effect of semen collection method (artificial vagina compared to electroejaculation), season in which the semen was collected (breeding season compared to non-breeding season), freezing extender (Biladyl(®), Andromed(®) and skim milk based extender) and pre-treatment procedure (washing compared to non-washing) on post-thaw semen quality in buck. Ejaculates from seven bucks of the Blanca-Celtibérica breed were collected by artificial vagina and electroejaculation during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 39 publications
(47 reference statements)
5
55
1
2
Order By: Relevance
“…It has been proven that ejaculates collected by artificial vagina have a lower percentage of sperm DNA fragmentation. Also, sperm samples collected during the breeding season in specific extenders presented better sperm quality [52]. …”
Section: Causes Of Dna Fragmentationmentioning
confidence: 99%
“…It has been proven that ejaculates collected by artificial vagina have a lower percentage of sperm DNA fragmentation. Also, sperm samples collected during the breeding season in specific extenders presented better sperm quality [52]. …”
Section: Causes Of Dna Fragmentationmentioning
confidence: 99%
“…Salmani et al [83] have suggested the use of soyabeanlecithin which is a suitable plant based cryoprotectant for caprine sperms. The beneficial effects of soyabean-lecithin as a substitute for egg yolk during cryopreservation of goat sperm are established in the works of Jiménez-Rabadán et al, Roof et al, Salmani et al, and Vidal et al [84][85][86][87].…”
Section: Cattlementioning
confidence: 99%
“…Thus, extenders based on soybean or extenders containing sugars with high molecular weight combined with permeable cryoprotectants such as glycerol has been studied for conventional sperm freezing in different species [2,6,[16][17][18]27,34]. Moreover, some investigations have been aimed to evaluate the effect of using permeable cryoprotectants [36], sucrose [37], or even a cryoprotectants-free technique joined to other preservation methods such as vitrification [11,13,36].…”
Section: Introductionmentioning
confidence: 99%